ФОРМУВАННЯ СОЦІАЛЬНО-ПРЕДМЕТНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ ТЕХНОЛОГІЇ У ХОДІ ПРОВЕДЕННЯ ЛАБОРАТОРНИХ ПРАКТИКУМІВ (Педагогіка вищої та середньої школи, 2008)
The practical orientation of works of laboratory practical works is the necessary condition of achievement by the future specialists of necessary level of subject knowledges and abilities of select profession as grounds of forming of socially-object competency